Cornulitids from the Upper Devonian of the Central Devonian Field, Russia. (2nd January 2019) - Vinn, Olev; Musabelliu, Sabiela; Zatoń, Michał
ABSTRACT: Two species of cornulitids, Cornulites devonicus and C. sokiranae sp. nov., commonly occur on Upper Devonian (Upper Frasnian and Lower Famennian) brachiopod shells in the area of the Central Devonian Field in Russia. Previously, C. devonicus was assigned to the serpulid species Serpula devonica . However, the present study shows that it is not a serpulid polychaete but a cornulitid with a microlamellar shell microstructure. Both Upper Devonian cornulitids are devoid of pseudopunctae and vesicular wall structures; the absence of the former in these species presumably does not constitute a useful adaptation. The greatest number of cornulitid species occurs in the Lower Devonian; their numbers seem to be lower in the Middle and Upper Devonian than in the Ordovician and Silurian. There are very few similarities between cornulitid faunas found in different palaeogeographical areas in the Devonian.